Intermittent parathyroid hormone enhances the healing of medication-related osteonecrosis of the jaw lesions in rice rats - E. J. Castillo; J. M. Jiron; C. S. Croft; D. G. Freehill; C. M. Castillo; J. Kura; J. F. Yarrow; I. Bhattacharyya; D. B. Kimmel; J. Ignacio Aguirre (Frontiers in Medicine, 2023)
Medication-related osteonecrosis of the jaw (MRONJ) is a potentially severe adverse event in patients treated with antiresorptives. Management of MRONJ is challenging, and no non-antibiotic, established medical treatment exists. Intermittent parathyroid hormone (iPTH) has been used off-label to treat MRONJ with favorable results. However, its medical efficacy has rarely been substantiated in clinical or preclinical experiments. Using a validated rice rat, infection-based model of MRONJ, we evaluated the effects of iPTH on established MRONJ. We hypothesize that iPTH contributes to MRONJ resolution by enhancing alveolar bone turnover and healing oral soft tissues. Eighty-four rice rats began a standard rodent chow diet at age 4 weeks to induce localized periodontitis. Rats were simultaneously randomized to receive saline (vehicle, VEH) or zoledronic acid (ZOL, 80 μg/kg IV) every 4 weeks. Oral exams were conducted bi-weekly to assign a gross quadrant grade (GQG, 0–4) to evaluate any lesion at the lingual aspect of the interdental space between maxillary molar (M2) and M3. 14 of 20 VEH-treated rice rats (70%) developed maxillary localized periodontitis with GQG 2–3 after 30 ± 10 weeks of saline. Additionally, 40 of 64 ZOL-treated rice rats with periodontitis developed MRONJ-like lesions after 30 ± 10 weeks of ZOL treatment. Rice rats with localized periodontitis or MRONJ-like lesions were treated with saline or iPTH (40 μg/kg) subcutaneously (SC) 3 times/week For 6 weeks until euthanasia. We found that iPTH -treated ZOL rats had a lower prevalence of MRONJ (p < 0.001), with lower severity extent of oral lesions (p = 0.003) and percentage of empty osteocyte lacunae (p < 0.001). ZOL rats treated with iPTH displayed a higher osteoblast surface (p < 0.001), more osteoblasts (p < 0.001), higher osteoclast surface (p < 0.001) and more osteoclasts (p = 0.002) at alveolar bone surfaces than ZOL/VEH rats. Greater gingival epithelial thickness and epithelial cell proliferation rate was found in the oral mucosa and gingiva of ZOL/PTH rats than in ZOL/VEH rats (p < 0.001). Our data suggest that iPTH is an efficacious non-operative medicinal therapy that accelerates oral healing and enhances the resolution of MRONJ lesions in ZOL-treated rice rats.